Relationship Between Maternal Employment and The Incidence of Stunting - Monica, Laily Prima; Agustina, Ika; Noviasari, Ita (Health Gate, 2025)
Stunting cases continue to increase along with the high risk of malnutrition, increasing prevalence of malnutrition, and decreasing productivity. Several factors related to the incidence of stunting in toddlers include birth weight, history of infectious diseases and birth spacing. This research identifies the relationship between maternal employment and the incidence of stunting in children. The research design was cross-sectional, carried out on a population of mothers with toddlers, all of whom were taken as a sample of 20 people. Instruments used in collecting questionnaire data. The results of this study show that there is a significant relationship between maternal employment and the incidence of stunting, with a p value of 0.000 (p ≤ 0.05). These data imply that maternal employment plays an important role in children's nutritional attainment. Employment status is directly related to the household's ability to provide quality and sufficient food.